Kualitas Pelayanan Administrasi Berbasis Program Online Cak3p - Putra, Alif Arkan; Syehabudin, Erik; Setiawan, Slamet; Nurlukman, Adie Dwiyanto (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
Electronic-based administrative services support the CAK3P online program in the Jurumudi Baru Village. The CAK3P online program is a form of e-service in the form of online birth certificate and death certificate services which also have similar values ​​such as Efficiency, Fulfillment, System Availability, Responsiveness, Privacy, Compensation, and Contact. There is an indirect relationship between the e-service concept and the CAK3P online service program. This study aims to determine the Quality of Administrative Services Based on the CAK3P Online Program in Jurumudi Baru Village. This study uses a qualitative approach using observation and interview techniques in collecting research data. In the CAK3P online program, the staff's timeliness in promising the issuance of birth and death certificates has not been maximized because there are still people who complain about the timeliness that does not match working hours and also the availability of an online system, there are still problems with the main application, so from Meanwhile, the community is still not satisfied with the CAK3P online program service.